Strategic Development of Taman Rejeki Group in Advancing Renewable Energy Contributions in Indonesia's Energy Transition - Putra, Azan Rahmadian; Putro, Utomo Sarjono (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the strategic development of Taman Rejeki Group in achieving its 500 MW renewable energy target by 2030. Using a hybrid methodology that combines PESTLE analysis, Porter’s Five Forces, and scenario planning the research identifies the driving factors and uncertainties influencing the company's renewable energy strategy. The study employs backcasting to work backward from the target goal outlining strategic steps to overcome identified barriers and capitalize on opportunities. The results of this research findings key uncertainties renewable energy in Indonesia such as PPA Terms & Conditions and Political Will are explored with four potential future scenarios developed suggest that Taman Rejeki Group must adopt flexible strategies aligned with these scenarios aggressive expansion in the stark protocol scenario with favorable conditions, efficiency and cash flow protection in the wakanda shield scenario with high-risk PPA, adaptation to sudden changes in the time loop strategy scenario with volatile political climates, and a survival strategy in the dark night plan scenario with regressive policy conditions. These strategies will ensure that the company can navigate varying political, regulatory, and financial environments, driving progress toward the 500 MW target by 2030.